Polyamine: A Potent Ameliorator for Plant Growth Response and Adaption to Abiotic Stresses Particularly the Ammonium Stress Antagonized by Urea - Sheng, Song; Wu, Changzheng; Xiang, Yucheng; Pu, Wenxuan; Duan, Shuhui; Huang, Pingjun; Cheng, Xiaoyuan; Gong, Yuanyong; Liang, Yilong; Liu, Laihua (Frontiers in Plant Science, 2022)
Polyamine(s), a sort of N-containing and polycationic compounds synthesized in almost all organisms, has been recently paid considerable attention because of its multifarious actions in the potent modulation of plant growth, development, and response to abiotic/biotic stresses. Polyamines in cells/tissues occur mainly in free or (non- or) conjugated forms by binding to various molecules including DNA/RNA, proteins, and (membrane-)phospholipids, thus regulating diverse molecular and cellular processes as shown mostly in animals. Although many studies have reported that increase in internal polyamine may be beneficial to plant growth under abiotic conditions, leading to a suggestion of improving plant stress-adaption by elevation of endogenous polyamine via supply or molecular-engineering of its biosynthesis, such achievements focus mainly on polyamine homeostasis/metabolism rather than polyamine-mediated molecular/cellular signalling cascades. Here, to advance our understanding of polyamine biological actions important for plant stress acclimation, we gathered some significant research data to succinctly describe and discuss in general polyamine synthesis/catabolism, as well as polyamine being as an internal ameliorator to regulate stress adaptions. Particularly, for the recently uncovered phenomenon of urea-antagonized NH4+-stress, from a molecular and physiological perspective we rationally proposed the possibility of an existence of polyamine-facilitated signal transduction pathways in plant tolerance to NH4+-stress. This may be a more interesting issue for deeply understanding of polyamine-involved growth acclimation to miscellaneous stresses in future studies.